Expression of interleukin-6 and its receptor subunits in the microenviroment of renal cell cancer - Karczewska, Aldona; Mackiewicz, Andrzej; Mackiewicz-Wysocka, Małgorzata; Kwias, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2001)
Renal cell cancer (RCC) is the most common adult cancer of the kidney. IL-6 plays an important role in pathogenesis of the RCC. IL-6 exhibits multiple biological activities such as regulation of immunological responses, promotion of acute inflammation and haematopoesis. IL-6 is produced by monocytes, macrophages, fibroblasts, endothelial cells, T and B cells and also by many different cancer cells, including RCC cells. IL-6 also stimulates proliferation of RCC cells. IL-6 exerts its activity via its receptor complex which consists of two subunits: alpha (gp80) and beta (gp130). We decided to evaluate the expression of mRNA encoding IL-6 and for alpha and beta subunits of IL-6 receptor in tumors and healthy kidney tissue. Cancer cells from tumors were isolated and cultured in vitro. In 44 patients, 18 women and 26 men nephrectomy due to RCC was performed. Total RNA was isolated from tumors, healthy tissues and from cultured cells. After reverse transcription obtained DNA was amplified using primers for IL-6 and for alpha and beta subunits of IL-6 receptor. We demonstrated expression of IL-6 mRNA in 45% of healthy tissues, in 77% of cancer tissues and in 54% of cancer cells cultured in vitro. The alpha and beta subunits of IL-6 receptor were expressed in 59% and 70% of healthy tissues, in 84% and 82% of cancer tissues and in 70% and 57% of cultured cells respectively. We demonstrated higher expression of IL-6 in renal cell carcinoma microenvironment, than in healthy kidney tissues. The tumor cells were mostly the main source of studied factors. Obtained results indicate that IL-6 and its receptor subunits are present in the microenvironment of RCC and may play a role in the pathogenesis of renal cell carcinoma in vivo.